Specific features of protein biosynthesis in higher eukaryotes - El'skaya, A.V.; Negrutskii, B.S.; Shalak, V.F.; Vislovukh, A.A.; Vlasenko, D.O.; Novosylna, A.V.; Lukash, T.O.; Veremieva, M.V. (Вiopolymers and Cell, 2013)
Over 40 years of studies in the field of higher eukaryotic translation are summarized in the review. Among the pioneer results obtained we should especially accentuate the following: i) discovery of the adaptation of tRNAs and aminoacyl-tRNA synthetases (ARSs) cellular pools to the synthesis of specific proteins and modulation of the elongation rate by rare isoacceptor tRNAs; ii) the chaperone-like properties of the translation components (ribosomes and elongation factor eEF1A); characterization of high molecular weight complexes of ARSs; iii) functional compartmentalization, including channeling of tRNA in eukaryotic cells; iv) molecular mechanisms of channeling mediated by different non-canonical complexes involving eEF1A, tRNA and aminoacyl-tRNA synthetases; v) characterization of the crystal structure of eEF1A2; vi) comparison of spatial structure, molecular dynamics, tyrosine phosphorylation and abilities to interact with different protein partners of the eEF1A1 and eEF1A2 isoforms; vii) discovery of the microRNA-mediated control of the expression of the proto-oncogenic eEF1A2 isoform in cancer cells; viii) examination of the cancer-related changes in translation elongation complex eEF1H and mechanisms of oncogene PTI-1 action; ix) discovery of the third tRNA binding site on mammals ribosomes and the allosteric interaction of the 80S ribosomal A and E sites. В огляд підсумовано найвагоміші результати більш ніж сорокалітніх досліджень особливостей трансляції у вищих евкаріотів, з-поміж яких: 1) відкриття адаптації клітинних пулів тРНК і аміноацил-тРНК синтетаз (АРСаз) до синтезу специфічних білків і модуляції швидкості елонгації рідкісними ізоакцепторними тРНК; 2) визначення шапероноподібних властивостей компонентів апарату трансляції (рибосом і фактора елонгації eEF1A), характеристика високомолекулярних комплексів АРСаз; 3) встановлення функціональної компартменталізації, у тому числі каналювання тРНК в евкаріотних клітинах; 4) з’ясування молекулярних механізмів каналювання, що відбувається за посередництвом різних неканонічних комплексів, які містять eEF1A, тРНК і АРС-ази; 5) характеристика кристалічної структури eEF1A2; 6) порівняння просторової організації, молекулярної динаміки, тирозинового фосфорилювання і здатності до взаємодії з різними білками – партнерами ізоформ eEF1A1 i eEF1A2; 7) виявлення ролі мікроРНК у контролі експресії протоонкогенної ізоформи eEF1A2 в ракових клітинах; 8) вивчення спричинених раком змін комплексу факторів елонгації трансляції eEF1H і механізмів дії онкогену PTI-1; 9) відкриття третього сайта зв’язування тРНК у рибосомах ссавців та алостеричної взаємодії А- і Е-сайтів 80S рибосоми. В обзоре суммированы наиболее значимые результаты более чем сорокалетнего исследования особенностей трансляции у высших эукариот, среди них: 1) открытие адаптации клеточных пулов тРНК и аминоацил-тРНК синтетаз (АРСаз) к синтезу специфических белков и модуляции скорости элонгации редкими изоакцепторными тРНК; 2) определение шапероноподобных свойств компонентов аппарата трансляции (рибосом и фактора элонгации eEF1A) и характеристика высокомолекулярных комплексов АРСаз; 3) установление функциональной компартментализации, включающей каналирование тРНК в эукариотных клетках; 4) выяснение молекулярных механизмов каналирования, опосредованного неканоническими комплексами, содержащими eEF1A, тРНК и АРС-азы; 5) характеристика кристаллической структуры eEF1A2; 6) сравнение пространственной организации, молекулярной динамики, тирозинового фосфорилирования и способности к взаимодействию с различными белками – партнерами изоформ eEF1A1 и eEF1A2; 7) выявление роли микроРНК в контроле экспрессии протоонкогенной изоформы eEF1A2 в раковых клетках; 8) изучение связанных с раком изменений комплекса факторов элонгации трансляции eEF1H и механизмов действия онкогена РТІ-1; 9) открытие третьего сайта связывания тРНК в рибосомах млекопитающих и аллостерического взаимодействия А- и Е-сайтов на 80S рибосомах.